Community, Exposed Singularity and Death in Mrs Dalloway - López Sánchez-Vizcaíno, María Jesús (International Journal of English Studies, 2024)
This essay brings Virginia Woolf and Jean-Luc Nancy into dialogue, focusing on their similar critique of essentialized models of community and evocation of forms of being-with that derive from the experiences of singularity and death. It identifies two forms of community in Woolf’s novel Mrs Dalloway (1925). The first one corresponds to Nancy’s conception of the immanent community, built upon essence and fusion, and in which death is provided with an ideological meaning. In Woolf’s novel, this communitarian logic traverses the official, ritualistic way in which England has sublimated the death and loss caused by the First World War, and the repressive conventions and the authoritarian spirit of the governing classes. An alternative kind of community, however, is suggested in Mrs Dalloway, one that can be identified with Nancy’s conception of the inoperative community: a community of singular beings who share their finitude, exposure and death. Blanchot’s ideas on the transient community of lovers and Butler’s theorization of a ‘we’ based upon common vulnerability and loss also shed light on this novel’s concern with antisocial bonds between characters that escape traditional forms of affiliation.